2011
DOI: 10.1002/chem.201101993
|View full text |Cite
|
Sign up to set email alerts
|

Deprotonative Metalation of Chloro‐ and Bromopyridines Using Amido‐Based Bimetallic Species and Regioselectivity‐Computed CH Acidity Relationships

Abstract: A series of chloro- and bromopyridines have been deprotometalated by using a range of 2,2,6,6-tetramethylpiperidino-based mixed lithium-metal combinations. Whereas lithium-zinc and lithium-cadmium bases afforded different mono- and diiodides after subsequent interception with iodine, complete regioselectivities were observed with the corresponding lithium-copper combination, as demonstrated by subsequent trapping with benzoyl chlorides. The obtained selectivities have been discussed in light of the CH aciditie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 106 publications
1
35
0
3
Order By: Relevance
“…18 Also, the treatment of 1b with a mixture of ZnCl 2 $TMEDA and [(TMP)Li] provides a mixture of C-2 and C-4 substituted product. 19 Clearly, different methodologies afford different products depending upon the reaction conditions and the type of the reagents used. A survey of the literature reveals no report on the BF 3 -directed lithiation of 3-chloro-and 3-bromopyridine with LDA and lithium tetramethylpiperidide (LTMP) as the lithiating reagent.…”
Section: Introductionmentioning
confidence: 99%
“…18 Also, the treatment of 1b with a mixture of ZnCl 2 $TMEDA and [(TMP)Li] provides a mixture of C-2 and C-4 substituted product. 19 Clearly, different methodologies afford different products depending upon the reaction conditions and the type of the reagents used. A survey of the literature reveals no report on the BF 3 -directed lithiation of 3-chloro-and 3-bromopyridine with LDA and lithium tetramethylpiperidide (LTMP) as the lithiating reagent.…”
Section: Introductionmentioning
confidence: 99%
“…The regioselectivity corresponds to combined acidifying and congesting effects of the bromo groups. [27] A clean C(4) deprotonation of 2,6-dibromopyridine (19a) can be performed by using LiCl-activated hinTa ble 3. Substituent effects on the rates of benzyne formation from ortho-, meta-, and para-substituted bromobenzenes (k rel , relative to bromobenzene for which k rel = 1).…”
Section: Long-range Effect Of Bromine In the Deprotometalation Of Benmentioning
confidence: 99%
“…It was found that metalation of 20 with organozinc [49,50] or magnesium agents [51] occurred selectively at the C-2 position of the pyridine ring ( Table 6, Entry 1). It was found that metalation of 20 with organozinc [49,50] or magnesium agents [51] occurred selectively at the C-2 position of the pyridine ring ( Table 6, Entry 1).…”
Section: Introductionmentioning
confidence: 99%